2016
DOI: 10.1073/pnas.1617427113
|View full text |Cite
|
Sign up to set email alerts
|

Antagonists of growth hormone-releasing hormone receptor induce apoptosis specifically in retinoblastoma cells

Abstract: Retinoblastoma (RB) is the most common intraocular cancer in children worldwide. Current treatments mainly involve combinations of chemotherapies, cryotherapies, and laser-based therapies. Severe or late-stage disease may require enucleation or lead to fatality. Recently, RB has been shown to arise from cone precursor cells, which have high MDM2 levels to suppress p53-mediated apoptosis. This finding leads to the hypothesis that restoring apoptosis mechanisms in RBs could specifically kill the cancer cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Human ocular cell lines, including retinal pigment epithelial (RPE) cells ARPE-19 (catalogue number: CRL-2302, American Type Culture Collection (ATCC), Manassas, VA) [11,12], lens epithelial cells B3 (catalogue number: CRL-11421, ATCC) [13], primary trabecular meshwork (TM) cells [14], and retinoblastoma cells Y79 (catalogue number: HTB-18, ATCC) [15], have been previously established. We also collected human mesenchymal stem cells (MSCs) from different sources, including bone marrow-derived MSCs (BM-MSCs; catalogue number: 7500; ScienceCell Research Laboratories, Carlsbad, CA) [16], adipose-derived stem cells (ASCs) [17], and periodontal ligament-derived stem cells (PDLSCs) [18,19].…”
Section: Human Cell Lines and Mouse Tissuesmentioning
confidence: 99%
“…Human ocular cell lines, including retinal pigment epithelial (RPE) cells ARPE-19 (catalogue number: CRL-2302, American Type Culture Collection (ATCC), Manassas, VA) [11,12], lens epithelial cells B3 (catalogue number: CRL-11421, ATCC) [13], primary trabecular meshwork (TM) cells [14], and retinoblastoma cells Y79 (catalogue number: HTB-18, ATCC) [15], have been previously established. We also collected human mesenchymal stem cells (MSCs) from different sources, including bone marrow-derived MSCs (BM-MSCs; catalogue number: 7500; ScienceCell Research Laboratories, Carlsbad, CA) [16], adipose-derived stem cells (ASCs) [17], and periodontal ligament-derived stem cells (PDLSCs) [18,19].…”
Section: Human Cell Lines and Mouse Tissuesmentioning
confidence: 99%
“…To investigate the molecular pathways regulated by the GHRH-R antagonist in apoptosis, mRNA was extracted from MIA-602-treated cells and subjected to reverse transcription coupled with quantitative real-time PCR (qRT-PCR). In our previous study, 5 we have found that GHRH-R antagonist suppresses ERK1 expression and induces Casp3 expression in retinoblastoma cells. In pterygium cells, we observed that MIA-602 could also significantly suppress ERK1 expression and induce Casp3 expression in a dose-dependent manner (Fig.…”
Section: Ghrh-r Antagonist Induced Apoptosis Through Suppression Of Ementioning
confidence: 85%
“…The relative ERK1 and Casp 3 mRNA expression in each sample was calculated as described previously. 5,8…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations